Impact of Mafic Underplating and Mantle Depletion on Subsequent Rifting: A Numerical Modeling Study. Issue 7 (2nd July 2019) - Chenin, Pauline; Jammes, Suzon; Lavier, Luc L.; Manatschal, Gianreto; Picazo, Suzanne; Müntener, Othmar; Karner, Garry D.; Figueredo, Patricio H.; Johnson, Christopher
Abstract: Orogenesis in the Variscan belt of Western Europe was followed by a major magmatic event during the Permian that formed a mafic lower crust by crystallizing pyroxenite and gabbros from mantle‐derived melts at the base of the continental crust. Partial melting of the asthenosphere left a significantly depleted mantle that was progressively incorporated into the subcontinental lithospheric mantle as the orogenic domain cooled. The potential impact of such large‐scale thermal and lithologic layering has never been taken into account in the study of the Alpine Tethys and North Atlantic rift systems that developed subsequently in Western Europe. Here we investigate via numerical modeling how a mafic heterogeneity within the lowermost part of a quartzo‐feldspathic continental crust and/or a zone of depleted mantle within the lithospheric mantle beneath a former orogenic domain could have influenced subsequent rifting. Our numerical modeling results indicate that, in a thermally equilibrated lithosphere, a mafic body within the lower continental crust or a zone of shallow depleted mantle prevents rifting of overlying weaknesses (e.g., faults and suture zones). We propose that the regional mafic lower crust beneath the Variscan orogenic domain may explain why the Tethyan and southern North‐Atlantic rift systems did not localize at former suture zones of the Western European orogenic lithosphere. Key Points: Mafic underplating of the crust generally prevents rifting of overlying weaknesses The North Atlantic and Alpine Tethys rifts avoided the underplated Variscan domain in Western Europe